Durabilitas Clay Shale Hambalang Lapuk Distabilisasi dengan Semen Portland dan Energi Pemadatan Berlebih - Ega Yogaswara; Idrus M. Alatas (Institut Sains dan Teknologi Nasional, 2022)
Abstrak The mechanical properties of clay shale are very unique. When dry it will shrink and harden, but when it absorbs water, it swells and to some extent loses its shear strength so that falling forces can occur suddenly even with its own weight. Due to its swell-shrink nature which is strongly influenced by climate and weather, the durability of clay shale can decrease over time when it comes into direct contact with air and water. Clay shale research was carried out in Hambalang, Bogor - West Java, Indonesia in the Jatiluhur formation, using weather stabilization stabilized with portland cement and excess compaction energy. with dynamic slaking (slake durability test). The dynamic slacking test was carried out three times, namely after sampling, 10, 20, and 30 blows/layer compaction were performed. With a low plasticity index, the durability research in Hambalang is classified as moderate to medium-high durability. Then, a test of excess compaction energy was carried out on variations in the stabilization of portland cement by increasing additional pressure. To determine the effect of the stabilization of portland cement with a composition of 5%, 10%, and 15% on clay shale, it showed an increase in the slake durability index, with the highest value in a mixture of 10% PC. The sample with an additional 15% PC and with an energy of 30 blow + pressure shows the highest Slake Durability Index value of 93.52%. However, this behavior cannot return to the original condition of clay shale (fresh clay shale). Keywords: Clay shale, durability, Slaking index, portland cement